LETRAMENTO CORPORAL NO BRASIL: UMA REVISÃO DOS ESTUDOS ASSOCIADOS À EDUCAÇÃO FÍSICA (REMUNOM, 2025)
The main objective of this article is to analyze the scientific production in Brazil on body literacy, with a focus on its application in the field of physical education. This study is characterized as a Systematic Literature Review, applied to five national and international databases, with a temporal scope from 2001 to 2025. Among the main results, it was found that the studies involve children and adolescents, primarily at the elementary school level. It was also observed that the findings include both quantitative and qualitative characteristics, with a preference for reports of experience and intervention aimed at proposing pedagogical actions. Therefore, due to the scarcity of studies on the subject, it can be said that working with body literacy still presents a challenge for both the scientific community and physical education teachers. To overcome these challenges, investments in ongoing professional development, improvements in school infrastructure, the enhancement of physical education, and a curricular approach that fosters the holistic development of students through body literacy are needed.